TLR4 Participates in the Inflammatory Response Induced by the AAF/II Fimbriae From Enteroaggregative Escherichia coli on Intestinal Epithelial Cells - Alvestegui, Alejandra; Olivares-Morales, Mauricio; Muñoz, Ernesto; Smith, Rachel; Nataro, James P.; Ruiz-Perez, Fernando; Farfan, Mauricio J. (Frontiers in Cellular and Infection Microbiology, 2019)
Enteroaggregative Escherichia coli (EAEC) infections are one of the most frequent causes of persistent diarrhea in children, immunocompromised patients and travelers worldwide. The most prominent colonization factors of EAEC are aggregative adherence fimbriae (AAF). EAEC prototypical strain 042 harbors the AAF/II fimbriae variant, which mediates adhesion to intestinal epithelial cells and participates in the induction of an inflammatory response against this pathogen. However, the mechanism and the cell receptors implicated in eliciting this response have not been fully characterized. Since previous reports have shown that TLR4 recognize fimbriae from different pathogens, we evaluated the role of this receptor in the response elicited against EAEC by intestinal cells. Using a mutual antagonist against TLR2 and TLR4 (OxPAPC), we observed that blocking of these receptors significantly reduces the secretion of the inflammatory marker IL-8 in response to EAEC and AAF/II fimbrial extract in HT-29 cells. Using a TLR4-specific antagonist (TAK-242), we observed that the secretion of this cytokine was significantly reduced in HT-29 cells infected with EAEC or incubated with AAF/II fimbrial extract. We evaluated the participation of AAF/II fimbriae in the TLR4-mediated secretion of 38 cytokines, chemokines and growth factors involved in inflammation. A reduction in the secretion of IL-8, GRO and IL-4 was observed. Our results suggest that TLR4 participates in the secretion of several inflammation biomarkers in response to AAF/II fimbriae.